The efficiency of selective pooling strategy in a COVID-19 diagnostic laboratory - Rebriarina Hapsari; Irfan Kesumayadi; Nani Maharani; Endang Mahati; Ferdy Kurniawan Cayami; Sutopo Patria Jati (Journal of Infection in Developing Countries)
Introduction: Mass testing is essential in the surveillance strategy for fighting the COVID-19 pandemic. It allows early detection of suspected cases and subsequently early isolation to mitigate spread. However, the high cost and limited consumables and reagents hinder the mass testing strategy in developing countries such as Indonesia. The specimen pooling strategy is an option to perform mass screening with limited resources. This study aims to determine the positivity rate cut-off and to evaluate the efficiency of pooling strategy for the laboratory diagnosis of COVID-19.